Expression profile, clinical significance, and biological function of insulin-like growth factor 2 messenger RNA-binding proteins in non–small cell lung cancer. Issue 4 (April 2017) - Shi, Run; Yu, Xinnian; Wang, Yajing; Sun, Jing; Sun, Qi; Xia, Wenjie; Dong, Gaochao; Wang, Anpeng; Gao, Zhaojia; Jiang, Feng; Xu, Lin
Insulin-like growth factor 2 messenger RNA-binding proteins have been described to associate with malignant process in many cancers. However, the role of insulin-like growth factor 2 messenger RNA-binding protein family has not been thoroughly elucidated in non–small cell lung cancer. This study was to investigate the expression profile, clinical significance, and biological function of insulin-like growth factor 2 messenger RNA-binding proteins family in non–small cell lung cancer. The expression levels of IGF2BP1–IGF2BP3 in tumor and adjacent normal tissues were determined, and association with clinicopathological features and overall survival was investigated by analyzing The Cancer Genome Atlas lung cancer database. Proliferation, migration, invasion assays, and flow-cytometry analysis were used to investigate the biological function in vitro. Insulin-like growth factor 2 messenger RNA-binding protein expression levels were significantly increased in non–small cell lung cancer compared to adjacent normal lung tissues. Chi-square test indicated that IGF2BP1 and IGF2BP3 expressions correlated with some meaningful clinical characteristics in non–small cell lung cancer. Kaplan–Meier analysis showed that high-level expression of IGF2BP1 or IGF2BP3 predicted poor overall survival in lung adenocarcinoma patients. Multivariate regression analysis showed that high level of IGF2BP3 was an independent risk factor for poor prognosis in lung adenocarcinoma patients (hazard ratio = 1.616, p = 0.017). In vitro, knockdown of IGF2BP3 inhibited lung adenocarcinoma cell proliferation by inducing cell cycle arrest and apoptosis, and undermined abilities of migration and invasion, and overexpression of IGF2BP3 could promote malignant phenotypes in lung adenocarcinoma cells. Our study revealed that expression of insulin-like growth factor 2 messenger RNA-binding proteins was widely upregulated and correlated with some certain clinicopathological features in non–small cell lung cancer. Especially, in insulin-like growth factor 2 messenger RNA-binding protein family, IGF2BP3 might play the most important role in tumor aggressiveness and prognosis in lung adenocarcinoma, and IGF2BP3 might serve as a potential therapeutic target and a novel prognostic biomarker in lung adenocarcinoma patients.